2017
DOI: 10.1103/physreve.95.032910
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effect of thresholding on temporal statistics of avalanches

Abstract: Avalanchelike behavior reflected in power-law statistics is a ubiquitous property of extended systems addressed in a number of generic models. The paper presents an experimental investigation of the effect of thresholding on the statistics of durations and waiting times between avalanches using acoustic emission accompanying unstable plastic deformation. It is found that durations of acoustic events obey power-law statistical distributions robust against thresholding. The quiescent time distributions follow th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
2
16
0
1
Order By: Relevance
“…It was verified (cf. [30,31]) that it renders relatively good estimates of power-law exponents, close to the values obtained by rigorous approaches based on the maximum-likeihood estimation with goodness-of-fit tests [32,33]. The histograms were calculated using equal bin sizes.…”
supporting
confidence: 53%
“…It was verified (cf. [30,31]) that it renders relatively good estimates of power-law exponents, close to the values obtained by rigorous approaches based on the maximum-likeihood estimation with goodness-of-fit tests [32,33]. The histograms were calculated using equal bin sizes.…”
supporting
confidence: 53%
“…Thresholding is a procedure applied to data either intentionally, or effectively due to the device limitations in experimental measurements where the thresholding cannot be avoided 31 . So, let the response signal of the system under study be V ( t ), let V ( t ) > 0 at any moment of time t when system is active (otherwise, let V ( t ) = 0), and let the system evolution proceeds in time separated connected bursts of activity, called avalanches.…”
Section: Resultsmentioning
confidence: 99%
“…(5) Although PDF dependences allow for an intuitively clear interpretation of different behaviors [39], a correct evaluation of power laws is a delicate task, and more exact methods were suggested recently [40,41]. Nevertheless, the comparison of estimates of the power-law exponents obtained by different methods showed that direct calculation of PDF renders reliable results for the PLC effect, providing that the low probability of rare large events is handled accurately [37,42]. The method of bin coupling was used for this purpose.…”
Section: Experiments and Data Analysismentioning
confidence: 99%